2017
DOI: 10.1111/acer.13321
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Review of the Effects of Nicotine and Alcohol Coadministration in Human Laboratory Studies

Abstract: Simultaneous use of cigarettes and alcohol is common and may be driven by nicotine increasing alcohol self-administration or vice versa. To better evaluate the causal nature of this relationship, we systematically reviewed human experimental laboratory studies that coadministered nicotine and alcohol with control conditions. Searches of PubMed/MEDLINE and PsycINFO databases and study bibliographies identified 30 studies that met our inclusion criteria. Research methodologies were critically reviewed. Effects o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 51 publications
(227 reference statements)
0
14
0
Order By: Relevance
“…There are several potential pharmacological, genetic, and environmental reasons for these high levels of co-use and maintenance of smoking among people with AUDs (Adams, 2017; McKee and Weinberger, 2013; Roche et al, 2016). For example, alcohol increases craving for nicotine and nicotine self-administration (Dermody and Hendershot, 2017; Verplaetse and McKee, 2017). Treatment programs for AUDs may present an important opportunity to aid these individuals with smoking cessation efforts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several potential pharmacological, genetic, and environmental reasons for these high levels of co-use and maintenance of smoking among people with AUDs (Adams, 2017; McKee and Weinberger, 2013; Roche et al, 2016). For example, alcohol increases craving for nicotine and nicotine self-administration (Dermody and Hendershot, 2017; Verplaetse and McKee, 2017). Treatment programs for AUDs may present an important opportunity to aid these individuals with smoking cessation efforts.…”
Section: Discussionmentioning
confidence: 99%
“…Although there may be concerns about providing smoking treatment concurrent with alcohol treatment, most studies find that concurrent smoking and alcohol treatment do not yield worse outcomes than treating alcohol alone (for recent reviews, see McKelvey et al, 2017; Thurgood et al, 2016). As cigarette use increases craving to use alcohol (Cooney et al, 2007; Dermody and Hendershot, 2017; Verplaetse and McKee, 2017), is related to decreased cognitive recovery in adults with AUDs (Durazzo et al, 2006, 2014; Pennington et al, 2013), and is associated with poorer AUD outcomes (Durazzo and Meyerhoff, 2017; Weinberger et al, 2015), combined smoking and alcohol treatment may offer significant benefits for alcohol treatment outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, studies suggest greater cravings to use alcohol when smoking cigarettes (see Dermody and Hendershot, 2017 for a review) and smoking may be associated with poorer long-term AUD outcomes (e.g., Weinberger et al, 2015). Notably, some studies have found improved alcohol and drug outcomes when those in treatment for alcohol and substance use disorders are also treated for tobacco use (McKelvey et al, 2017; Thurgood et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Risk of harmful drinking is even higher among those who engage in nondaily tobacco use compared to daily tobacco use (McKee et al, 2007, Harrison et al, 2008). Preclinical and human laboratory studies indicate that tobacco use may increase risk of harmful drinking (Verplaetse and McKee, 2017, Dermody and Hendershot, 2017, Kohut, 2017). Tobacco potentiates the reinforcing effects of alcohol (Piasecki et al, 2011), which may explain the high rate of episodic co-administration among people who use both substances (McKee and Weinberger, 2013).…”
Section: Introductionmentioning
confidence: 99%